Skończone Odkształcenia Niesprężystych, Wiotkich, Obrotowo-Symetrycznych Powłok Ortotropowych - Orkisz, J. (Engineering Transactions, 1967)
The object of the present paper is to derive the Eqs. (2.13) in the case of the theory of plastic flow and (2.17) in the case of the strain theory describing in the course of the loading process the behaviour of a flexible, cyrcularly symmetric orthotropic shell in a membrane state under finite anelastic deformation. The physical relations are assumed in the form (1.1) or (1.9) which are valid if the directions of orthotropy coincide with the principal directions and remain invariable in the course of the loading process. They relate the true stresses with the logarithmic strains and constitute a generalization of the Nádai-Davis equations [30], into the case of an orthotropic material. Tensile stress being the only one transmitted by the shell stresses, two cases are considered in which a) both principal stresses are positive (σ1 > 0, σ2 > 0), b) the circumferential stress is zero (σ2 > 0, σ2 = 0). Finally, an elementary example is given for an infinite orthotropic cylindrical shell subject to a constant internal pressure and a tensile axial force. The present paper constitutes a generalization of Refs. [33 and 34] of the present author, to the case of an orthotropic material.